Day 2 Tue, November 08, 2016 2016
DOI: 10.2118/183068-ms
|View full text |Cite
|
Sign up to set email alerts
|

Multistage Horizontal Hydraulic Fracture Optimization Through an Integrated Design and Workflow in Apollonia Tight Chalk, Egypt from the Laboratory to the Field

Abstract: The key challenge in unconventional gas plays covering vast geographical areas is locating the regions in the reservoir with the highest combination of reservoir and completions quality. This allows operators to evaluate not only the richness of their resource but also the ability of the reservoir to produce hydrocarbons in commercial quantities. This paper discusses hydraulic fracturing designs targeting tight gas in horizontal wells drilled in the Apollonia tight chalk formation in the Abu-Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…We had one leakoff test record (7988 PSI at 10,362 ft) from the overlying shales of the AR-E Member which exhibited a S hmin gradient of 0.77 PSI/ft. The interpreted AR-F S hmin gradient corroborates well with the published interpretation from the JDT field and Al-Khilala fields located in the onshore Nile Delta region (Salah et al, 2016;Leila et al, 2021). Considering a normal faulting stress state and an effective maximum horizontal stress ratio (k) of 0.5, we infer a S hmax gradient of 0.88 PSI/ ft.…”
Section: Rock-mechanical Properties and Brittleness Indexsupporting
confidence: 88%
“…We had one leakoff test record (7988 PSI at 10,362 ft) from the overlying shales of the AR-E Member which exhibited a S hmin gradient of 0.77 PSI/ft. The interpreted AR-F S hmin gradient corroborates well with the published interpretation from the JDT field and Al-Khilala fields located in the onshore Nile Delta region (Salah et al, 2016;Leila et al, 2021). Considering a normal faulting stress state and an effective maximum horizontal stress ratio (k) of 0.5, we infer a S hmax gradient of 0.88 PSI/ ft.…”
Section: Rock-mechanical Properties and Brittleness Indexsupporting
confidence: 88%
“…Stewart (1999) suggested that gas accumulations at shallow depths can cause enough overpressure to form set of faults and fractures with a circular structure. An important observation, however, is that the chalk reservoir of the Apollonia Formation is characterized by its low formation pressure (Elmahdy et al, 2018;Salah et al, 2016) which suggests the releasing of the formation pressure after the generation of the polygonal faults.…”
Section: Discussionmentioning
confidence: 99%
“…The Apollonia Formation (upper Paleocene to middle Eocene) is overlain by the Dabaa Shale (Oligocene), and is underlain by the chalk of the Khoman Formation (Upper Cretaceous) ( Figure 3). The Apollonia Formation was studied in detail in terms of its lithology, palaeontological characteristics and reservoir productivity (e.g., El-Bendary et al, 2016;Elmahdy, Farag, Tarabees, & Bakr, 2018;Salah, Orr, Abdel Meguid, Crane, & Squires, 2016;Sedek & Al Mahdy, 2013;Sousa & Badri, 1996).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Ongoing explorations and studies aim at identifying optimal technologies to maximize productivity of unconventional low-permeability reservoirs [30]. [41] and [42] summarized the findings of the recent activities within different unconventional plays in Egypt from which the basis for necessary subsequent development could be achieved.…”
Section: Fig 1-annual Petroleum and Other Liquids Production And Conmentioning
confidence: 99%